(untitled) (PILAR, 2022)
Abstract Syariahic economics and conventional economics are two different economic systems which from time immemorial have become one of the determining factors for success in the economic development of a country and even the world economy. This study aims to describe the application and contribution of the two economic systems in building the country’s economy. This study uses a qualitative approach with library research, which is a series of activities carried out with regard to the method of collecting library data, or studies explored through various library information. (books, encyclopedias, scientific journals, newspapers, magazines, and documents), which discuss the Conventional Economic System and the Syariahic Economic System. The results of the study show that the Conventional Economic System consists of 2 economic systems, namely; 1) Capitalism economic system that developed because of the policies of colonialism and imperialism that affect Asian and African countries where this system is based on the struggle for freedom where the government may not take part in its implementation. 2) a socialist economic system that arises as a result of protests over injustices applied to the capitalist economic system where the rich are getting richer, and the poor are getting poorer, this is the socialist economic system that comes with providing considerable freedom but with a note that the government takes part in its implementation. Furthermore, the Syariahic Economic System is an economic system that has finally become a solution to various problems that have arisen so far. and the poor are getting poorer, this is a socialist economic system that comes with providing considerable freedom but with a note that the government takes part in its implementation. Furthermore, the Syariahic Economic System is an economic system that has finally become a solution to various problems that have arisen so far. and the poor are getting poorer, this is a socialist economic system that comes with providing considerable freedom but with a note that the government takes part in its implementation. Furthermore, the Syariahic Economic System is an economic system that has finally become a solution to various problems that have arisen so far. Keywords: Syariahic Economics; Economics of Capitalism, Economics of Socialism